Bariatric Surgery From the Non-Surgical Approach to the Post-Surgery Individual Care - Saiz-Sapena, Nieves; Miguel Oviedo, Juan (IntechOpen, 2021)
Written by experts in the field of bariatrics, this edited volume reviews the multidisciplinary process of treating the obese patient, from the reception of the obese patient and their dietary, social, and psychological evaluations to individual management, discharge, and follow-up. It offers a holistic approach, providing the knowledge required to implement treatment effectively. Chapters cover surgical procedures in the abdomen, physical exercise, psychological and social support, nutritional strategies, and pharmacologic options. This book is a valuable resource for physicians, surgeons, bariatric anesthesiologists, nutritionists, psychologists, nurses, physical therapy specialists, and others involved in the care of obese and overweight patients.